ALLERGY TEST OF TUBA ROOT EXTRACTS ON SKIN OF LOCAL KITTENS - Siswanto, Siswanto; Sulabda, I Nyoman; Soma, I Gede (Buletin Veteriner Udayana, 2016)
Tuba root (Derris elliptica) contains a toxin rotenone which is an isoflavone compounds (flavonoids) included in the group of phenolic compound, which can kill fish and insects, including ticks and mites. Tuba root can be used as antiektoparasit in animals (eg fleas in cats), however research on skin sensitization of kitten to tuba extract was less or even not exist. This research used experimental animals; 6 kittens aged 1-3 months (unnoticed sexes) were divided randomly into two groups, three as a control (K) and three as treatment (P). Cats shorn size of 0.5 cm x 0.5 cm in the nape, abdominal and groin, then drops (one drop) the tuba root extract concentration of 15%, 20% and 25%. After 30, 60, and 120 minutes, visible signs that the onset of allergic skin itchy, red, or inflamed. The design used was completely randomized analysis method uses a variant level of 5%. Further data tested by LSD 5%. Results showed that the tuba root extract concentration of 15%, 20% or 25% did not cause an allergic on kitten skin (not significant p>0.05). It concluded that the tuba root extract is safe and can be used for anti-parasite in kittens aged 1-3 months.
Keywords: ekstrak akar tuba; alergi; anak kucing; tuba roots extract; allergy; kittens